Bioadhesive thin film formulation using the ultrasonic stent sprayer - Lim, Sharon See Man. (2012)
In tackling the problem of blocked coronary artery, an alternative to heart bypass is angioplasty balloons. Over the years, there have been many improvements to the balloons such as the development of Bare Metal Stents (BMS) and Drug Eluting Stents (DES). Although DES dealt efficiently with some of the problems of BMS, there is still another problem of late stent thrombosis. Hence, there is much interest in Drug Eluting Balloons (DEB) that does not bring this problem but presents more benefits with the paclitaxel drug coated on it.